Magnetism and magnetic properties of Ti-rich titanomagnetite and its tendency for alteration in favour of titanomaghemite - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2010)
The study of the Ti-rich titanomagnetite (Ti-Mt) and the low-temperatureoxidized Ti-Mt bearing basalts has been undertaken. High magnetic susceptibility of theTi-rich Ti-Mt basalts does not correspond to high spontaneous magnetization. The decreaseof spontaneous magnetization with increasing content of ulv¨ospinel is evidenced.The spontaneous magnetization in ferromagnetics and ferrimagnetics originate in the magneticdomains, but the domain structure in the Ti-rich larger Ti-Mt grain sizes is rarelydeveloped. The cause of high magnetic susceptibility of the Ti-rich Ti-Mt stems probablyfrom the molecular field of the two sub-lattice structure of the Ti-Mt.Alternative explanation: In the low magnetic fields, the permeability of the mixedferrites increases with increasing temperature and reaches the extreme maximum at thetemperature closely below the Curie temperature of material. Similar behaviour havebeen shown also by the Ti-rich Ti-Mt-es. Rapid decrease of the magnetic crystalographicanisotropy with temperature and the decrease in intensity of the exchange interactionsare responsible for this effect. So, the increase of Ti4+ ions in the titanomagnetite resultsin the increase of magnetic susceptibility of the Ti-rich Ti-Mt-es.The problem of the extremely low magnetic susceptibility in the basalts with lowtemperatureoxidized phase consists in the following: along with the low-temperature oxidationof Fe2+ to Fe3+ ion and the formation of vacancies in creating titanomaghemite,the rearrangement of magnetic moments in initial Ti-rich Ti-Mt has taken place. Theinitial state had a more anti-ferromagnetic arrangement with high content of ulv¨ospinelof high non-collinearity. High magnetism of the initial Ti-Mt was due to the action ofthe molecular field. During the above-mentioned process this original state was brokendown, and the magnetic susceptibility was rapidly decreased. A completely new ferrimagnneticarrangement of magnetic moments of the sub-lattices has been established inthe titanomaghemite.